Constitutionality Holding Sub Holding SOEs in the Field of Electricity Supply Business: Konstitusionalitas Holding Sub Holding BUMN di Bidang Usaha Penyediaan Ketenagalistrikan - Adhistianto, Mohammad Fandrian (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
This research discusses the limitations on the privatization of State-Owned Enterprises (BUMN) in the field of electricity supply and itscorrelation with the implementation of the sub holding structure inPT PLN (Persero). This discussion is crucial, given that electricity is avital sector of production for the nation and profoundly impacts thewell-being of the general populace, necessitating state control. The studyadopts a normative legal research approach, employing conceptualframeworks and secondary data. The research’s conclusion is that theconstitution restricts the privatization of State-Owned Enterprises in theelectricity supply sector, emphasizing that only State-Owned Enterprisesare authorized to manage electricity-related businesses. National orforeign private companies are only permitted to participate if invitedto collaborate by State-Owned Enterprises. The implementation of thesub holding structure in PT PLN (Persero), utilizing the shareholderscheme involving Geothermal Co and New Energy Co as subsidiaries,contradicts the 1945 Constitution because it leads to an escape fromstate control.